Results of an Open, Non-placebo Controlled Pilot Study Investigating the Immunomodulatory Potential of Autovaccine - Rusch, Volker; Ottendorfer, Doris; Zimmermann, Kurt; Gebauer, Frank; Schrödl, Wieland; Nowak, Peter; Skarabis, Horst; Kunze, Rudolf (Arzneimittelforschung, 2001)
Autovaccines are prepared from autologous, human, non-pathogenic, “rough” variants of E. coli derived from the stool flora of individuals according to a highly standardized procedure. As a fundamental concept within microbiological therapy, these autovaccines are mainly used to treat chronic inflammatory disorders associated with impaired immune reactions resistant to standard therapeutic treatments. Generally, immunomodulatory effects of outer membrane components or cell wall fragments of gram-negative bacteria on innate or adaptive immunity are widely accepted but nevertheless mechanisms of actions of these auto-vaccines remained obscure, despite some recent publications about other autovaccine preparations of different origin. Hence, immunomodulating properties of autovaccine were investigated in a pilot study with 78 outpatients with variable disorders ranging from recurrent respiratory infections to diffuse gastrointestinal complaints. Patients received their autologous bacteria parenterally in increasing doses. Before application and 4 to 6 weeks after application of autovaccine, blood samples of the patients were taken to investigate a range of immunological parameters such as acute phase proteins, serum antibodies and cytokines. The results revealed that autovaccines were able to modulate significantly the release of three potent immunoregulatory cytokines e.g. interferon-γ, granulocyte-macrophage-colony stimulating factor and in-terleukin-1beta, whereas specific humoral immunity remained largely unaffected. From these results it may be concluded that the autovaccine mainly act antigen non-specifically on the cytokine level rather than inducing a specific vaccination. Further studies with more detailed kinetic measurements of cytokines will have to verify these results.
Keywords: Autovaccine, acute-phase proteins, cellular immunity, cytokines, humoral; immunity, rough E. coli